GEOLOGI BAWAH PERMUKAAN KAITANNYA DENGAN POTENSI PELULUKAN / LIKUIFAKSI DI DAERAH ERETAN DAN LOSARANG, JAWA BARAT - Lumbanbatu, U. M.; Hidayat, S. (Jurnal Geologi dan Sumberdaya Mineral, 2011)
The investigated area which belongs to the coastal plain is composed of Quaternary sediments such as soil, swamp, near shore, offshore and pre-Holocene sediments. Further more, near shore sediment can be divided into sand flat, mixed flat, mud flat and beach sand. In general those sediments are still loose and water saturated. Among beach sand, sand flat and mix flat have a high level of vulnerability to liquefied. Based on seismic data, an occurrence of earthquakes can be triggered by two earthquake sources namely subduction sources. An earthquake took place on August 8, 2007 at 04:58 known as Indramayu Earthquake is an example of eartquake triggered by subduction zone since the quake has a depth of 289.2 Km with a magnitude of M 7.5 on the Richter scale. From the geological aspect and seismicity point of view the investigated area is potential for experience liquefaction events. Based on the physical properties of the sand deposits and their stratigraphical position as well as other factors such as a thickness of sand layer, types of overlay and underlain sediments then a liquefaction susceptibility in this region can be divided into very low liquefaction susceptibility region, low liquefaction susceptibility region and high liquefaction susceptibility region.Keywords: quaternary, earthquakes, liquefaction, Inramayu